The Pine Branch, March 1933 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1933)
The Pine Branch. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
The Bounds of GossipDoris Zittrouer 3 | Have You Heard?Marjorie Sessions 6 | Poem: Breezesby Marie Louise Blair 9 | A "Stag"? At a GirLBreak DanceVirginia Martin 10 | Willie Paul's Sermon About "Nory's Flood"? Louise McMichael 12 | Editorial | Locals | Critical Tips 16 | Clubs IS | Y W C A 20 | Societies 21 | Athletics 23 | Alumnae 24 | Jokes 26 | Campus Chatter 27
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education